STRATEGI GURU DALAM MENINGKATKAN LITERASI MEMBACA PADA PELAJARAN TEMATIK DI SDIT AL-HUDA DESA PETALA BUMI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Milah, Jejen Jaenal; Maulidin, Syarif; Muhammad Latif Nawawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading literacy is one of the fundamental skills that must be developed in elementary school students to support learning success and improve critical thinking abilities. However, students’ reading interest and literacy skills are still relatively low, especially in thematic learning. This study aims to describe the strategies used by teachers in improving reading literacy in thematic learning at SDIT Al-Huda Petala Bumi, Seberida District, Indragiri Hulu Regency. This research employed a qualitative descriptive approach. The subjects of the study consisted of teachers and students at SDIT Al-Huda. Data were collected through observation, interviews, and documentation. The findings revealed that teachers implemented various strategies to improve students’ reading literacy, including the habituation of reading activities for 15 minutes before lessons, the provision of reading corners, guided reading methods, the use of visual and digital learning media, literacy programs such as Kamis Literasi (KALIS), and collaboration with parents in supporting literacy activities at home. Teachers also provided motivation and rewards to increase students’ interest in reading. The study found that these integrated strategies were effective in improving students’ reading habits, comprehension skills, and participation in thematic learning. Therefore, teachers play an important role as facilitators, motivators, and innovators in creating a literacy-supportive learning environment in elementary schools.